2019
DOI: 10.1038/s41598-019-53218-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-genomic effects of the Pregnane X Receptor negatively regulate platelet functions, thrombosis and haemostasis

Abstract: The pregnane X receptor (PXR) is a nuclear receptor (NR), involved in the detoxification of xenobiotic compounds. Recently, its presence was reported in the human vasculature and its ligands were proposed to exhibit anti-atherosclerotic effects. Since platelets contribute towards the development of atherosclerosis and possess numerous NRs, we investigated the expression of PXR in platelets along with the ability of its ligands to modulate platelet activation. The expression of PXR in human platelets was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…In other organizations, the total levels and the activation levels of specific SFK members were also important for regulating apoptotic activity 28 . Flora et al reported that down-regulation of SFKs activity negatively regulated platelet functions, thrombosis, and haemostasis 29 . All in all, SFKs are the key to regulating the life activities of the body of every aspect.…”
Section: Structure and Biological Characteristics Of Sfksmentioning
confidence: 99%
“…In other organizations, the total levels and the activation levels of specific SFK members were also important for regulating apoptotic activity 28 . Flora et al reported that down-regulation of SFKs activity negatively regulated platelet functions, thrombosis, and haemostasis 29 . All in all, SFKs are the key to regulating the life activities of the body of every aspect.…”
Section: Structure and Biological Characteristics Of Sfksmentioning
confidence: 99%
“…Testing platelet function in response to genetic mutations, gene knockouts, and pharmacological agents is a valuable and widely used assay in platelet research [1][2][3][4][5][6][7][8]. In these studies, the analysis of platelet spreading, either by the calculation of adhesion levels, spread surface areas or morphological categorization, is used as a measure of platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of washed platelets, immunoblotting, immunofluorescence, and platelet functional assays such as aggregation, dense granule secretion, fibrinogen binding, P-selectin exposure, calcium mobilization, clot retraction, platelet spreading, thrombus formation, and tail bleeding were performed as described previously. 26,27,[30][31][32] Detailed descriptions of reagents and these methods are provided in supplemental Methods (available on the Blood Web site).…”
Section: Methodsmentioning
confidence: 99%